มูลค่าผลิตภาพแรงงานผู้สูงอายุของจังหวัดสุราษฎร์ธานี - ช่างคิด นันทวรรณ; ทวีพงษ์ พรทิพย์ (Journal of Business, Innovation and Sustainability (JBIS), 2020)
The research aims to study the working conditions of the elderly, to measure the productivity value and variables affecting the productivity value, and to determine the appropriate wage for the elderly in Suratthani, Data were collected from 392 participants and were analyzed using frequency, percentage, median, mean, standard deviation and Multiple Regression Equation. The findings showed that mostly of participants were female, aged 61-64 years old, married and have lived with family. Their education was less than or equal to the 7th grade. The original works were farmers and traders. Their income was less than 10,000 baht. Currently they were farmers, traders and workers. They work at home as an independent job; earn income from work and government subsidies. They expense less than 5,000 baht, no saving, and any debt. They have high blood pressure. They work 5-6 hours every day. Their production is 470-560 baht; wage is 300 baht per day and no benefits. Wage and trade work affected to the productivity, the coefficients equal 1.373 and 90.061. It meant that when wage rise by 1% and they do trade work, productivity will rise 1.373%and 90.061%. The duration of work’s coefficient was -24.055, when the duration of work rise by1%, productivity will decline 24.055%.The productivity of the tradesmen and non-tradesmen were 717.92 and 627.85, however, they were paid 327.90 baht per day. The merit wage should be 415 baht per day. Keywords: 1) Value Productivity of labour 2) elderly worker3) Informal sector.